2015
DOI: 10.1002/pbc.25676
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Fundamental Movement Skills in Childhood Cancer Patients

Abstract: This study highlighted the significant deficits in FMS within pediatric patients having completed cancer treatment. In order to reduce the occurrence of significant FMS deficits in this population, FMS interventions may be warranted to assist in recovery from childhood cancer, prevent late effects, and improve the quality of life in survivors of childhood cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Twelve months post treatment, two-thirds of children scored below the 50 th percentile on the movement ABC. Neuman et al [ 24 ] compared the FMS proficiency of pediatric cancer survivors with a reference group of 300 healthy children. Cancer survivors were significantly less likely to exhibit mastery on seven key FMS (sprint run, vertical jump, side gallop, leap, catch, kick, overarm throw) than healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve months post treatment, two-thirds of children scored below the 50 th percentile on the movement ABC. Neuman et al [ 24 ] compared the FMS proficiency of pediatric cancer survivors with a reference group of 300 healthy children. Cancer survivors were significantly less likely to exhibit mastery on seven key FMS (sprint run, vertical jump, side gallop, leap, catch, kick, overarm throw) than healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…However, these limitations were not only limited to motor skills. Physical movement skills like balance, jumping, running as well as muscle strength were also found to be impaired (22, 23). Therefore, the results of deficits in HRPF line up with these previously noted functional and physical impairments (24).…”
Section: Discussionmentioning
confidence: 99%
“…In children 0-2 years of age, the Bayley Infant Scoring system for neurocognitive development has been routinely used and is both reliable and valid [71]. If the child has developed basic movement skills (walk, run, throw, skip, hop, leap) then an assessment of fundamental movement skills may be appropriate [72,73]. Nauman et al have reported the performance efficiency on the sprint run, vertical jump, side gallop, leap, catch, kick, and overarm throw efficacy in childhood cancer patients, which discriminated between oncology patients and health controls [72].…”
Section: Motor and Skill Assessmentmentioning
confidence: 99%
“…The primary goal in the initial phase of exercise prescription for CCS is to make the activity fun and promote motor skill development as motor skill proficiency is related to increased lifetime physical activity [77]. The programs need not be performance-based and careful instruction on movement patterns should be encouraged [72]. Adherence to specific sets and repetitions should be encouraged, while fatigue and improper postural alignment or biomechanics should serve as an indicator to terminate the specific exercise.…”
Section: Recommendationsmentioning
confidence: 99%